Re: Request for submitting shop drawing for PV roof and jogging track steel structure - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reply on request for submitting shop drawing for PV roof and jogging track steel structure of BRACU new campus project.